Penerapan Digital Marketing dalam Aplikasi Lazada untuk Membangun Brand Awarness - Sunur, Arba; Pradana, Wahyu Yuda; Abrar, M Farid; Nurbaiti (Jurnal Informatika, Multimedia dan Teknik, 2024)
This study discusses the application of digital marketing in the Lazada application to build brand awareness. By utilizing social media as a digital marketing strategy. The study uses qualitative methods by collecting data from several journal and book sources with the Literature Review method. The results of the study indicate that Brand Awareness is very necessary in the company, with the implementation of strong Brand Awareness it will have a positive impact on the company because consumer awareness of a brand greatly influences the success of a company. This study concludes that Lazada has implemented several marketing strategies to increase Brand Awareness to introduce their products such as; brand ambassadors, advertising promotions, competitor research, providing promotions.